Improved training in mathematics for engineering students: e-courses - Rozhkova S. V. Svetlana Vladimirovna; Rozhkova V. I. Valentina Ivanovna; Lasukov V. V. Vladimir Vasilievich; Chervach M. Yu. Mariya Yurievna (2017, 2017)
Title screen